Marriage, Divorce and Interstate Risk Sharing - Martin Halla; Johann Scharler (Johannes Kepler University of Linz, Department of Economics, 2008)
In this paper we study the importance of marriage for interstate risk sharing. We find that US states in which married couples account for a higher share of the population are less exposed to state-specific output shocks. Thus, marriages do not just improve the allocation of risk at the individual level, but also have implications for the allocation of risk at the more aggregated state-level. Quantitatively, the impact of marriage on interstate risk sharing varies over divorce regimes.
Keywords: J12; E21; K36; G21; 330; Risk sharing; marriage; divorce; family law; Ehe; Familienrecht; Familienökonomik; Risiko; Schock; Aggregation; Regionale Inzidenz; Teilstaat; USA